A new species of Crepidorhopalon (Linderniaceae) from the Mutinondo Wilderness, Zambia - Fischer, Eberhard; Darbyshire, Iain; Bingham, Mike (Phytotaxa, 2014)
The new species Crepidorhopalon mutinondoensis from Zambia is described and illustrated. It is closely related to Crepidorhopalon latibracteatus and C. parviflorus from which it differs in the glabrous calyx and bracts except for the minute hairs along the margins of each, and the smaller calyx and corolla. It differs from Crepidorhopalon symoensii in the entire bracts and the long peduncle. A key to the species of Crepidorhopalon with capitate inflorescence is provided.